2019
DOI: 10.3390/rs11141705
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Rebar Corrosion through the Combination of Nondestructive GPR and IRT Methodologies

Abstract: Corrosion is one of the pathologies that most affects the resistance of reinforced concrete. There are numerous ancient structures still in use affected by corrosion that need proper evaluation and remedial treatment for their maintenance. In this sense, there has been an increasing tendency to use nondestructive testing techniques that do not alter the reinforcement elements of such vulnerable structures. This work presents a combined methodology by using ground penetrating radar (GPR) and infrared thermograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…In experimental examination [10] where different exposure conditions were simulated by immersing corroded rebars in three different water oil emulsions, the emulsions with higher dielectric permittivity ensured an increase in travel time of reflected waves and decrease in amplitude. Similar observations about the relation between dielectric permittivity and signal attributes were made by other authors [7,20].…”
Section: Effect Of Moisture and Chloride Content On Gpr Datasupporting
confidence: 87%
“…In experimental examination [10] where different exposure conditions were simulated by immersing corroded rebars in three different water oil emulsions, the emulsions with higher dielectric permittivity ensured an increase in travel time of reflected waves and decrease in amplitude. Similar observations about the relation between dielectric permittivity and signal attributes were made by other authors [7,20].…”
Section: Effect Of Moisture and Chloride Content On Gpr Datasupporting
confidence: 87%
“…The analysis was based on the evaluation of B-scans and A-scans, detecting changes on the amplitude of the reflected signal and changes in the blurring of the images. Previous reported works (e.g., [15,17,22]) have shown that corrosion could be identified both in B-scans due to blurred images and in A-scans due to changes in the amplitude. In those cases, the change in the intensity was related to the chemical action of chlorides in the concrete as consequence of corrosion rebar.…”
Section: Discussionmentioning
confidence: 94%
“…The application of GPR to corrosion detection is usually tested in laboratory [21]. However, recent field studies have demonstrated the possibility of obtaining a quantitative approach of damage degree by combining GPR with other NDT survey such as infrared thermography [22]. This paper presents some controlled laboratory tests focused on the qualitative and quantitative analysis of GPR signal changes as consequence of corrosion.…”
mentioning
confidence: 99%
“…The amplitude value (or strength) of the reflected pulses is proportional to the dielectric contrast value between two media. The receiving antenna can be installed either in the same antenna box as the transmitting antenna or in a separate box [ 20 ]. It should be noted that an XZ image (typically called radargram) is obtained as a result of the GPR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the X axis represents the distance (meters) of each trace (position of each pulse received) and the Z axis represents the two-way travel time of the radar pulses through the media. In addition to the amplitude of reflection, other attributes of the received GPR signal can be studied such as the amplitude spectrum, the velocity of propagation, and the dielectric constant of the propagation medium [ 20 ].…”
Section: Introductionmentioning
confidence: 99%